TINJAUAN PEMBERIAN MAAF KELUARGA KORBAN KEPADA TERDAKWA DAN IMPLIKASINYA TERHADAP PUTUSAN HAKIM DALAM PERKARA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN KEMATIAN (Studi Putusan Pengadilan Negeri Jepara Nomor 87/Pid.Sus/2014/PN. Jpa) - Nathania Ratih K.P., dan Tonny Priyangga, Marina Kurnianingsih (GEMA, 2015)
This thesis speak abaout the problems is whether the victimâs family to pardon the accused in the case investigation of traffic accidents resulting in death in Jepara district court is in conformity with the provisions of the Criminal Procedure Code and the implications of the victimâs family to pardon the accused in the case of traffic accident investigation againts the decision of the judge in the District Court Jepara.Based on the results of this study concluded that the victimâs family to pardon the accused in the case investigation of traffic accidents resulting in death in Jepara District Court No. 87/Pid.Sus/2014 are testimony of the witness and testimony of the defendant as evidence that is valid and forgiveness as mitigating factors for the defendant in accordance with Article 184 paragraph (1) letter a and e in conjunction with Article 197 paragraph (1) of the Criminal Procedure Code. Implications for the victimâs family to pardon the accused in the case investigation of traffic accidents on the judgeâs decision that takes into account as mitigationcircumstances for the defendant has fulfilled the provisions of Article 197 paragraph (1) of the Criminal Procedure Code and declare the defendant was legally and convincingly guilty of criminal âDriving a motor vihicle due to negligence has caused a trffic accident that resulted in other people diedâÂ  in accordance with Article 310 paragraph (4) in conjuction with Article 229 paragraph (4) Law Decree 22 of 2009 on Traffic and Road Transport